Borehole logging from the Fucino Basin, hole F-4 - Thomas Wonik; Thomas Grelle; Katja Hesse; Christian Zeeden (PANGAEA, 2019)
Borehole logging data (gamma ray, magnetic susceptibility) from the the Fucino Basin, hole F-4. Data as in Giaccio et al. (2019), doi:10.1016/j.quascirev.2019.106003
Supplement to: Giaccio, Biagio; Leicher, Niklas; Mannella, Giorgio; Monaco, Lorenzo; Regattieri, Eleonora; Wagner, Bernd; Zanchetta, Giovanni; Gaeta, Mario; Marra, Fabrizio; Nomade, Sébastien; Palladino, Danilo M; Pereira, Alison; Scheidt, Stephanie; Sottili, Gianluca; Wonik, Thomas; Wulf, Sabine; Zeeden, Christian; Ariztegui, Daniel; Cavinato, Gian Paolo; Dean, Jonathan R; Florindo, Fabio; Leng, Melanie J; Macrì, Patrizia; Niespolo, Elizabeth M; Renne, Paul; Rolf, Christian; Sadori, Laura; Thomas, Camille; Tzedakis, Polychronis C (2019): Extending the tephra and palaeoenvironmental record of the Central Mediterranean back to 430 ka: A new core from Fucino Basin, central Italy. Quaternary Science Reviews, 225, 106003, https://doi.org/10.1016/j.quascirev.2019.106003